Complementation analysis of resistance to 5-fluorocytosine in Candida albicans. - Whelan, W L (1986)
A complementation test was devised to study allelism among the genetic determinants of resistance to 5-fluorocytosine in Candida albicans. Complementation was demonstrated in control hybrids produced by crossing a resistant strain that was deficient in cytosine deaminase activity with four other resistant strains deficient in UMP pyrophosphorylase activity. This complementation test was used to test allelism of the resistance determinants present in five clinical isolates. All were found to bear recessive alleles of the locus (FCY1) that determined 5-fluorocytosine resistance associated with low levels of UMP pyrophosphorylase activity.